Oxford international Lower Secondary English Workbook 1 for grade 6 for Grade 6 - Barber, Alison; Saunders, Mark (Karachi : Oxford university press, 2023)
The "Oxford International Lower Secondary English Student Workbook 2" for Grade 7 is designed to complement the main textbook, offering students additional practice to reinforce their English language skills. This workbook provides a variety of exercises focused on grammar, vocabulary, reading comprehension, and writing, tailored to the Grade 7 curriculum. Each section is aligned with the topics covered in the student book, allowing for a seamless integration of classroom learning and independent study. The exercises range from structured drills to creative tasks, encouraging both analytical and imaginative thinking. The workbook also includes self-assessment tools and progress checks to help students identify areas for improvement and build confidence in their language abilities. With clear instructions and engaging content, this workbook is an essential resource for enhancing language proficiency and achieving academic success in English.
Keywords: English-work book; Oxford english work book